Enhancing the Transferability of Adversarial Examples with Feature Transformation - Hao-Qi Xu; Cong Hu; He-Feng Yin (Mathematics, 2022)
The transferability of adversarial examples allows the attacker to fool deep neural networks (DNNs) without knowing any information about the target models. The current input transformation-based method generates adversarial examples by transforming the image in the input space, which implicitly integrates a set of models by concatenating image transformation into the trained model. However, the input transformation-based methods ignore the manifold embedding and hardly extract intrinsic information from high-dimensional data. To this end, we propose a novel feature transformation-based method (FTM), which conducts feature transformation in the feature space. FTM can improve the robustness of adversarial example by transforming the features of data. Combining with FTM, the intrinsic features of adversarial examples are extracted to generate transferable adversarial examples. The experimental results on two benchmark datasets show that FTM could effectively improve the attack success rate (ASR) of the state-of-the-art (SOTA) methods. FTM improves the attack success rate of the Scale-Invariant Method on Inception_v3 from 62.6% to 75.1% on ImageNet, which is a large margin of 12.5%.